FACTORS INFLUENCING THE INCOME ON HOUSEHOLDS FISHERMAN IN LIMBUNGAN VILLAGE RUMBAI PESISIR SUB DISTRICT PEKANBARU CITY RIAU PROVINCE - Walid Ramadhan; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This tudy was conducted on March to April 2016 at Limbungan village Rumbai Pesisir sub district Pekanbaru city Riau province. The method use is survey methodBased on the research that has been done toward the alternative business, of fishermen is farming, worker, commerce, strore service, ponsel service, and cleanning service. The Mean of income that accepted from fishing effort is IDR. 524.91-per month while the average mean that accepted from alternative affort is IDR. 1.126.666 –per month. Analysis result (R2) is 0,174 meaning factors income of work time (X1), amount of burden work (X2), age (X3), and educate (X4) have influence 17 % and show independent variabel can give influence 17 % while the average residue 83 % influence the another factor.Key words : factors income, fishing effort, alternative businesses.